Integrasi PIPRECIA dan MACROS Dalam Penentuan Lokasi Pertanian Berkelanjutan - Irma Hakim; Asdi Asdi; Oktoni Eryanto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study develops a decision support system for selecting sustainable agricultural locations amid the challenges of climate change. Two integrated multi-criteria decision-making (MCDM) methods are employed: PIPRECIA (Pivot Pairwise Relative Criteria Importance Assessment) to determine the importance weights of criteria based on expert rankings, and MACROS (Measurement Alternatives and Ranking according to the Compromise Solution), a structured method used to evaluate and rank alternatives through normalization, weighted scoring, and compromise-based ranking. Six key criteria are considered: water availability, land suitability, flood risk, market access, government support, and microclimate conditions. The integration of PIPRECIA and MACROS enables a systematic and transparent evaluation process. The results indicate that location